Population ageing patterns in Małopolskie voivodship by poviats until 2030 - Kurkiewicz Jolanta; Knapik Oskar (Bulletin of Geography. Socio-Economic Series, 2012)
The aim of the paper is to demonstrate differences and similarities in population structures of the poviats of Małopolskie voivodship in the years 2010‒2030, with particular attention to population ageing. To describe the ageing process two types of indicators are used, namely conventional and prospective measures. As conventional ones we assume the percentage of the population aged 65 and over, and the old-age dependency ratio expressed as the number of persons aged 65 and over per 100 persons aged 20‒64. The same aspects of population ageing are expressed by a new group of measures based on a fresh concept for measuring age, the so-called prospective age. Unlike chronological (retrospective) age, prospective age takes into account the changes in life expectancy that occur in the period under consideration. Using the data coming from Demographic Years Book 2011, and from Demographic Projection 2008‒2011 (www.stat.gov.pl) some types of population ageing patterns in Małopolskie voivodship by poviats until 2030 are demonstrated. They count both differences in population ageing of poviats in Małopolskie voivodship and the dynamics of this process in view of conventional and prospective measures. The general features of demographic ageing in Małopolskie voivodship in 2010‒2030 are formulated in conclusions.